Critical research impact: On making space for alternatives. Issue 2 (29th July 2019) - Machen, Ruth
Abstract : This paper argues for greater dialogue between critical research and research impact. With demands to demonstrate impact increasingly woven into the funding architectures of higher education, concerns have been raised that the UK Research Excellence Framework's impact agenda could adversely affect critical research, favouring instead research that more easily lends itself to societal uptake. Arguing that the threat to critical research is real but not inevitable, this paper draws from a review of impact case studies submitted to REF2014 to provide a perspective on what impact from critical research could look like, and the support required to encourage critical research within the UKREF Impact Agenda. Building on previous provocations to think about research impact differently, it is argued that impact can be conceptualised in ways that support critical agendas. Specifically, the paper identifies five modes of critical research impact: challenging policy; empowering resistances; platforming voices; nurturing new critical publics; and envisioning alternatives. These five modes signal potential for thinking about research impact in ways that support critical goals. Abstract : This paper argues that research impact can be conceptualised on critical terms, and in ways that support critical agendas. Informed by the impact case studies submitted to REF 2014, the paper identifies and discusses five possible modes of critical research impact: challenging policy; empowering resistances; platforming voices; nurturing new critical publics; and envisioning alternatives.